Essential thrombocythemia in young individuals: frequency and risk factors for vascular events and evolution to myelofibrosis in 126 patients - Alvarez-Larrán, A; Cervantes, F; Bellosillo, B; Giralt, M; Juliá, A; Hernández-Boluda, J C; Bosch, A; Hernández-Nieto, L; Clapés, V; Burgaleta, C; Salvador, C; Arellano-Rodrigo, E; et al. (Leukemia, 2007)
The frequency of vascular events and evolution to myelofibrosis (MF) in young individuals with essential thrombocythemia (ET) is not well known. The incidence and predisposing factors to such complications was studied in 126 subjects diagnosed with ET at a median age of 31 years (range: 5-40). Overall survival and probability of survival free of thrombosis, bleeding and MF were analyzed by the Kaplan-Meier method and the presence of the Janus Kinase 2 (JAK2) V617F mutation correlated with the appearance of such complications. The JAK2 mutation (present in 43% of patients) was associated with higher hemoglobin (Hb) (P<0.001) and lower platelets at diagnosis. With a median follow-up of 10 years (range: 4-25), 31 thrombotic events were registered (incidence rate: 2.2 thromboses/100 patients/year). When compared with the general population, young ET patients showed a significant increase in stroke (odds ratio 50, 95% CI: 21.5-115) and venous thromboses (odds ratio 5.3, 95% CI: 3.9-10.6). Thrombosis-free survival was 84% at 10 years, with tobacco use being associated with higher risk of thrombosis. Actuarial freedom from evolution to MF was 97% at 10 years. In conclusion, young ET patients have thrombotic events, especially stroke and venous thrombosis, more frequently than generally considered, whereas they rarely transform to MF.